2000
DOI: 10.3758/bf03212130
|View full text |Cite
|
Sign up to set email alerts
|

Attending, ignoring, and repetition: On the relation between negative priming and inhibition of return

Abstract: Aseries of spatial localization experiments is reported that addresses the relation between negative priming and inhibition ofreturn. The results of Experiment 1 demonstrate that slowed responses to repeated location stimuli can be obscured by repetition priming effects involvingstimulus dimensions other than spatial location. The results of Experiments 2, 3A,and 3B demonstrate that these repetition priming effects may occur onlywhen participants are required to respond to the prime display.Together, these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
173
4
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(202 citation statements)
references
References 58 publications
24
173
4
1
Order By: Relevance
“…The IOR account (Christie & Klein, 2001;Milliken et al, 2000) is also partially consistent with our results. Christie and Klein found that negative priming could be explained by IOR when everything else was perfectly balanced.…”
Section: Reconciling Our Theoretical Interpretation With Other Accountssupporting
confidence: 92%
“…The IOR account (Christie & Klein, 2001;Milliken et al, 2000) is also partially consistent with our results. Christie and Klein found that negative priming could be explained by IOR when everything else was perfectly balanced.…”
Section: Reconciling Our Theoretical Interpretation With Other Accountssupporting
confidence: 92%
“…TPJ may be specifically important for the detection of novel and behaviorally relevant stimuli (Asplund et al, 2010). A fundamental mechanism contributing to IOR is the relative lack of novelty of a target appearing at the same location of a previously presented cue, separated by long SOA (Milliken et al, 2000). IOR could be caused by a "habituation" of the orienting response some time after the cue has been presented (Milliken et al, 2000;Dukewich, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental mechanism contributing to IOR is the relative lack of novelty of a target appearing at the same location of a previously presented cue, separated by long SOA (Milliken et al, 2000). IOR could be caused by a "habituation" of the orienting response some time after the cue has been presented (Milliken et al, 2000;Dukewich, 2009). Such a phenomenon would bias attention toward locations that have not been previously attended or explored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Deschepper and Treisman (1998) Houghton & Tipper, 1994;Milliken Tipper, Houghton, & Lupianez, 2000) that similar processes mediate the inhibitory effects observed via cueing (e.g., IOR) and priming (e.g., negative priming). Therefore one might predict that retrieval of prior inhibitory states might be observed in both procedures.…”
Section: Introductionmentioning
confidence: 99%